Sprachen : Jenseits von Dichtung. - Marquardt, Axel; Schmidt, Siegfried J.; Dencker, Klaus Peter; Cobbing, Bob (Münster : Westfälischer Kunstverein, 1979)
Adler ; Attalai ; Badura ; Bäcker ; Bauer ; Ben ; Bentivoglio ; Blank ; Büttersdorf ; Brandl ; Carrion ; Claire ; Clark ; Claus ; Clavin ; Cobbing ; Cox ; Danon ; Dencker ; van Dijk ; Dimitrijevic ; Drozdz ; Esser ; Export ; Finlay ; Furnival ; Gappmayr ; Garnier ; Gerz ; Gibbs ; Criffiths ; Grimshaw ; Guben ; Gut ; Hell ; Hoogstraten ; Houédard ; Jandl ; etc.
Sprachen : Jenseits von Dichtung, Westfälischer Kunstverein, Münster, 1979
boek